Evaluation of contribution of micro and macro components to oxidative stability on virgin oils obtained from olives characterized by different health quality - Bendini, A.; GÓMEZCARAVACA, A. M.; Cerretani, L.; Del Carlo, M; Segura-Carretero, A.; Compagnone, D.; Cichelli, A.; Lercker, G. (Progress in Nutrition, 2007)
The high oxidative stability of extra virgin olive oil is mainly due to its fatty acid composition, in particular to the high monounsaturated-to-polyunsaturated ratio, and to the presence of minor compounds having phenolic structure, that also have a major role in preventing oxidation. Several classes of phenolic compounds have been identified in extra virgin olive oil (phenolic acids, phenyl ethyl alcohols, flavonoids, lignans and secoiridoids) and among them the secoiridoids (aglyconic derivatives of oleuropein and ligstroside) are the most abundant constituents. Phenolic compounds belonging to o-diphenolic category, such as oleuropein aglycon (OA), decarboxymethyl-oleuropein aglycon (DOA), and hydroxytyrosol (HYTY), are mainly responsible for the oxidative resistance of extra virgin olive oil. In this work, results dealing with oxidative stability (OSI) of several samples (n=32) obtained from olives with a different degree of Bactrocera oleae attack (0-85%), are shown. Moreover an electrochemical evaluation of the antioxidant power (AOP) of the phenolic fraction has been carried out. This method enables the recognition of the phenols that may be easily oxidised. Data demonstrate an increase of products coming from hydrolytic and oxidative degradations of fatty acids as a function of the degree of olive fly attack. Moreover, their negative contribution to oil stability has been established. Olives soundness influenced mainly the phenolic content of samples, which as a result, affected the OSI values. Fatty acid composition was involved to a lesser extent.